Influence of irbesartan on expression of ILK and its relationship with epithelial-mesenchymal transition in mice with unilateral ureteral obstruction - Liu Bi-cheng; Xia Hui-ling; Wu Ji-ning; Zhang Xiao-liang; Liu Dian-ge; Gong Yu-xiang (Acta Pharmacologica Sinica; Vol 28, No 11 (November 2007): Acta Pharmacologica Sinica, 2016)
Aim: Irbesartan, a new antagonist of the type 1 angiotensin II receptor, has been proven to be renal protective in both diabetic and non-diabetic nephropathy, but its exact mechanism is still uncertain. Here we investigated the influence of irbesartan on the expression of the integrin-linked kinase (ILK) and its relationship with epithelial-mesenchymal transition (EMT) in mice with unilateral ureteral obstruction (UUO). Methods: The mice were randomly divided into 3 groups: sham operation (C, n=20), UUO (n=40), and UUO with irbesartan treatment (UUO+irbesartan, n=40). Irbesartan was given at a dose of 50 mg/kg body weight per day by gavage. The experimental animals in the control group received the same volume of vehicle (0.9% saline solution). The animals were sacrificed at d 1, 3, 7, and 14, respectively, after the surgery. Results: The expression of the ILK at mRNA and protein levels were significantly increased in the UUO group 1 d after the surgery, which was significantly decreased by treatment with irbesartan (P